Comparison of Two Internet-Based Interventions for Problem Drinkers: Randomized Controlled Trial - Cunningham, John Alastair (JMIR Publications, 2012)
BackgroundAlcohol problems are a serious public health concern, and few problem drinkers ever seek treatment. The Internet is one means of promoting access to care, but more research is needed to test the best types of interventions to employ. Evaluation of Internet-based interventions that contain a variety of research-validated cognitive-behavioral tools, which have been shown to be helpful to those with more severe alcohol concerns, should be a priority. ObjectiveTo evaluate whether providing access to an extended Internet intervention for alcohol problems offers additional benefits in promoting reductions in alcohol consumption compared with a brief Internet intervention. The hypothesis for the current trial was that respondents who were provided with access to an extended Internet intervention (the Alcohol Help Center [AHC]) would display significantly improved drinking outcomes at 6-month follow-up, compared with respondents who were provided with access to a brief Internet intervention (the Check Your Drinking [CYD] screener). MethodsA single-blinded randomized controlled trial with a 6-month follow-up. A general population sample of problem drinkers was recruited through newspaper advertisements in a large metropolitan city. Baseline and follow-up data were collected by postal mail. ResultsA volunteer sample of problem drinkers of legal drinking age with home access to the Internet were recruited for the trial. Of 239 potential respondents recruited in 2010, 170 met inclusion criteria (average age 45 years; 101/170, 59.4% male; average Alcohol Use Disorders Identification Test [AUDIT] score of 22). Follow-up rates were 90.0% (153/170) with no adverse effects of the interventions reported. A repeated-measures multivariate analysis of variance of the outcome measures using an intent-to-treat approach found a significantly greater reduction in amount of drinking among participants provided access to the AHC than among participants provided access to the CYD (P = .046). ConclusionsThe provision of the AHC gave additional benefit in the short term to problem drinkers over that seen from the research-validated CYD, indicating the benefits of promoting access to these interventions as one means of helping people with problem drinking concerns. Trial RegistrationClinicalTrials.gov NCT01114919; http://clinicaltrials.gov/ct2/show/NCT01114919 (Archived by WebCite at http://www.webcitation.org/68t1dCkRZ)